ANALISIS DESA NYAMBU SEBAGAI DESA WISATA EKOLOGIS BERBASIS MASYARAKAT (JURNAL KEPARIWISATAAN, 2017)
Nyambu Village is Ecological Tourism Village which involves the local community in its development and management. The potencies of Nyambu Village as the ecological tourism village are biodiversity of flora and fauna, cultural diversity in the form of Balinese temple, indigenous art and ritual, local-structure community/cultural group and traditional game which still preserved until now. The method in this study is qualitative discriminative by observation, survey and in-depth interviews with community and management of tourism village. Random sampling technique is conducted to the community by distributing questionnaires to find out the public perception of principles factor of ecological tourism village. The development of Nyambu Village as an ecological tourism village is developed based on the principles of nature conservation, cultural conservation, community participation, economy, education and tourism. The result shows, the community perception score for conservation principles is 3.80; cultural conservation principles 3.82; principles of community participation 3.77; economic principles 3.65; 3.83 educational principles and 3.83 tourism principles. Based on the average scores recommends that the dominant factor on the principle of education and tourism.